2014
DOI: 10.2140/agt.2014.14.3259
|View full text |Cite
|
Sign up to set email alerts
|

Simplicial structures and normal forms for mapping class groups and braid groups

Abstract: In this paper we show that the mapping class groups of any surface with nonempty boundary form a simplicial group as the number of marked points varies. This extends the simplicial structure on braid groups of surfaces found by Berrick, Cohen, Wong and Wu. We use the simplicial maps to construct compatible normal forms for elements of the braid groups and mapping class groups of surfaces with boundary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Apart from the proof of Proposition 3.7, we do not consider the full mapping class groups here. Again, there is another extension of this result in [3], where it is shown that when the surface M has nonempty boundary then the pure (respectively, full) mapping class groups admit degeneracy maps as well as face maps, and therefore form a simplicial group (respectively, crossed simplicial group).…”
Section: The δ-Structure On Braid and Mapping Class Groupsmentioning
confidence: 82%
See 1 more Smart Citation
“…Apart from the proof of Proposition 3.7, we do not consider the full mapping class groups here. Again, there is another extension of this result in [3], where it is shown that when the surface M has nonempty boundary then the pure (respectively, full) mapping class groups admit degeneracy maps as well as face maps, and therefore form a simplicial group (respectively, crossed simplicial group).…”
Section: The δ-Structure On Braid and Mapping Class Groupsmentioning
confidence: 82%
“…We do not consider full braid groups in this paper. Another extension of this result occurs in [3], where it is shown that, when the surface M admits a nonvanishing vector field, the pure (respectively, full) braid groups may be endowed with degeneracy maps as well as face maps, and therefore form a simplicial group (respectively, crossed simplicial group). Next, we recall the Δ-group structure on the mapping class groups of a surface M .…”
Section: The δ-Structure On Braid and Mapping Class Groupsmentioning
confidence: 91%